How young adults perceive advertising: a comparative study of three ethnic groups - Hiram, Ting; Ernest Cyril, de Run (2013)
The aim of this study is determine attitude of young consumers towards advertising by ethnicity. Specifically, it seeks to understand how the young adults from the Iban, Chinese and Malay communities perceive advertising. A seven-factor belief model was adopted to decompose the theory of reasoned action in order to provide theoretical basis to examine whether there is any difference in beliefs and attitude towards advertising between the three ethnic groups. A quantitative approach via questionnaire-based survey was administered at universities. As a result, 316 out of 400 copies were collected for analyses. The finding show that despite cultural differences embedded in ethnic groups, the beliefs and attitude of the three ethnic groups towards advertising are largely found to be not significantly different. They can only be differentiated with the effect of beliefs on the formation of attitude towards advertising. Implications and future studies are provided.